KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN, DENGAN DIVIDEND PAYOUT RATIO SEBAGAI VARIABEL INTERVENING - Andyni Yulfanis Aulia Masrifa (STIE AUB Surakarta, 2016)
This research aimed of this study to analysisthe influence of the independent variables are characteristics of the firm (Firm Size, sales growth, DTA and ROA) toward firm value either directly or indirectly if the Dividen Payout Ratio is mediated on the manufacturing companies listed on the Indonesia Stock Exchange 2006-2010 period. Sampling selection used purposive sampling method.Analysis technique used is two-stageregressionanalysis(path analysis). Result of analysis show that the predictive ability of the four independent variables toward DPR andfirm valueare 18,1% and25,4%, it shown by adjusted R² value. Onthe goodness of fit testshows thatboth modelsfit for usebecause it hasa significance valuelessthan5% of alpha value. Based onTtestshowed that inmodel1, thesalesgrowthis positiveand significant impact of DPR, and DTA is negative and significant impact of DPR because it has a significance value less than 5% of Alpha value. And in model 2, firm size is positiveand significant impact of firm value, andROA is positive and significant impact offirm value.However, based ontestingthe mediationeffect, DPR not provedas anintervening variableon the relationshipcharacteristics of the firm(Firm Size, salesgrowth,DTAandROA) towardfirmvalue, becausethe coefficient ofthe directeffect ofthe characteristics ofthe firm (Firm Size, salesgrowth,DTAandROA) tofirm value is greater than theindirecteffectthrough DPR. Key Words: Firm Value, firm size, sales growth, ROA, DTA, DPRand Manufacturing Companies